The use of concrete slurry waste to improve the properties of the stabilised soil - Davidová, Vendula; David, Tomáš; Mondschein, Petr; Reiterman, Pavel (Acta Polytechnica CTU proceedings, 2024)
It is often necessary to use stabilising additives during construction to improve the resulting soil properties to ensure the good quality of civil engineering structures. These additives are often produced at high temperatures and with a high carbon footprint. This paper focuses on soil stabilization with waste concrete slurry, which is produced during the production of fresh concrete. The selected clay soil was stabilized with cement and CSW at 2, 4, and 6 % by weight of soil. Compressive strength, the resistance to freezing and thawing, Initial bearing index (IBI), and California bearing capacity (CBR) were monitored. The research did not confirm better performance of CSW binder even at higher dosage compared to cement, which was due to the high water content of the mixtures. Positive results were achieved especially in Freez-Thaw resistance.